The lymphocyte-to-monocyte ratio predicts intracranial atherosclerotic stenosis plaque instability - Wu, Xiao-Bing; Huang, Li-Xin; Huang, Zhong-Run; Lu, Li-Ming; Luo, Bin; Cai, Wang-Qing; Liu, An-Min; Wang, Sheng-Wen (Frontiers in Immunology, 2022)
Background and purpose: Gadolinium enhancement on high-resolution vessel wall imaging (HR-VWI) is an imaging marker of intracranial atherosclerotic stenosis (ICAS) plaque instability. This study aimed to evaluate the relationships between hematological inflammatory indicators and the enhancement of ICAS plaques and to search for hematological indicators that can predict ICAS plaque instability. Methods: Consecutive adult patients diagnosed with ICAS from April 2018 to December 2021 were recruited retrospectively, and every patient underwent HR-VWI. Plaque enhancement was measured qualitatively and quantitatively. The plaque-to-pituitary stalk contrast ratio (CR) indicated the degree of plaque enhancement. Clinical and laboratory data, including the lymphocyte-to-monocyte ratio (LMR), neutrophil-to-lymphocyte ratio (NLR), and systemic immune inflammation index (SII), were recorded. The hematological inflammatory indicators were compared between ICAS patients with and without plaque enhancement and between patients with and without symptomatic plaque. The hematological inflammatory indicators and the CR were compared using linear regression. Furthermore, receiver operating characteristic curve analysis was performed to assess the discriminative abilities of the inflammatory indicators to predict plaque instability. Results: Fifty-nine patients were included. The NLR, SII and LMR were significantly correlated with plaque enhancement. The LMR was independently associated with plaque enhancement, and a linear negative correlation was observed between the LMR and CR (R = 0.716, P < 0.001). The NLR, LMR, plaque enhancement and CR were significantly associated with symptomatic ICAS, and the LMR and plaque enhancement were independent risk factors for symptomatic ICAS. The optimal cutoff value of the admission LMR to distinguish symptomatic plaque from asymptomatic plaque was 4.0 (80.0% sensitivity and 70.6% specificity). Conclusion: The LMR was independently associated with ICAS plaque enhancement and showed a linear negative correlation with CR. The LMR and plaque enhancement were independent risk factors for symptomatic ICAS. An LMR ≤ 4.0 may predict ICAS plaque instability.